Optical and Chemical Analysis of Absorption Enhancement by Mixed Carbonaceous Aerosols in the 2019 Woodbury, AZ, Fire Plume. Issue 15 (10th August 2020) - Lee, James E.; Dubey, Manvendra K.; Aiken, Allison C.; Chylek, Petr; Carrico, Christian M.
Abstract: Wildfires emit mixtures of light‐absorbing aerosols (including black and brown carbon, BC and BrC, respectively) and more purely scattering organic aerosol (OA). BC, BrC, and OA interactions are complex and dynamic and evolve with aging in the atmosphere resulting in large uncertainties in their radiative forcing. We report microphysical, optical, and chemical measurements of multiple plumes from the Woodbury Fire (AZ, USA) observed at Los Alamos, NM, after 11–18 hr of atmospheric transit. This includes periods where the plumes exhibited little entrainment as well as periods that had become more dilute after mixing with background aerosol. Aerosol mass absorption cross sections (MAC) were enhanced by a factor of 1.5–2.2 greater than bare BC at 870 nm, suggesting lensing by nonabsorbing coatings following a core‐shell morphology. Larger MAC enhancement factors of 1.9–5.1 at 450 nm are greater than core‐shell morphology can explain and are attributed to BrC. MAC of OA (MACOrg ) at 450 nm was largest in intact portions of the plumes (peak value bounded between 0.6 and 0.9 m 2 /g [Org]) and decreased with plume dilution. We report a strong correlation between MACOrg (450 nm) with the fC2H4O2 (a tracer for levoglucosan‐like species) of coatings and of bulk OA indicating that BrC in the Woodbury Fire was coemitted with levoglucosan, a primary aerosol. fC2H4O2 and MACOrg (450 nm) are shown to vary between the edge and the core of plumes, demonstrating enhanced oxidation of OA and BrC bleaching near plume edges. Our process‐level finding can inform parameterizations of mixed BC, BrC, and OA properties for wildfire plumes in climate models. Plain Language Summary: Wildfires generate particles that can cool or warm climate regionally. Organic particles in the atmosphere typically cool climate by redirecting incoming light away from the Earth. Conversely, soot particles absorb light and can cause warming. Additionally, a specific type of organic particle called brown carbon absorbs light at visible and near‐ultraviolet wavelengths. Brown carbon's chemical composition and its ability to absorb light are not well understood, making its climate impacts highly uncertain. We estimate the absorption by aged smoke particles from the Woodbury Fire in Arizona at Los Alamos in New Mexico. Additionally, we propose a chemical tracer to estimate the absorption by brown carbon in wildfire plumes to simulate brown carbon climate impacts in climate models. Key Points: Observed aerosol absorption relative to pure BC was enhanced by a factor of 1.5–2.2 at 870 nm and 1.9–5.1 at 450 nm in wildfire plumes Absorption enhancements are attributed to organic aerosol coating black carbon and to brown carbon with derived absorption efficiencies Absorption efficiency at 450 nm correlated with the levoglucosan fraction in organic aerosol, implying levoglucosan can track brown carbon